Assessment of physicochemical and minerals of wastewaters from food industries in Makurdi, for irrigation purposes - Rose Erdoo Kukwa; Umbur Winifred Ukpoko; Luter Leke (Water Science)
The food processing industries produce large volumes of wastewaters but poor management has resulted to environmental problems. The reuse of such wastewaters as organic fertilizer containing essential plant nutrients for irrigational purposes is an attractive management strategy. The improper disposal and poor management of these wastewaters from some selected food industries within Makurdi, necessitated the assessment of the physicochemical characteristics, mineral constituents and water quality indices in comparison with FAO and WHO standard limits. Three (3) wastewater samples were collected from Seraph Oil Mill (SOWW), Miva Rice Nigeria Limited (MRWW), and Chile Fish Farm (CFWW). The wastewater samples were analyzed for the physicochemical properties and mineral elements using standard methods and micro-wave plasma atomic emission spectroscopy (MP-AES) respectively, and water quality indices calculated. The results of the physicochemical parameters revealed pH values ranging from 5.63 ± 0.57 to 7.60 ± 0.03, electric conductivity from 2.72 ± 0.01 to 206.5 ± 0.47 µScm−1, viscosity from 1.73 ± 0.01 to 93.3 ± 0.58 mPa.S, total solids (TS) ranged from 0.039 ± 0.001 to 3.02 ± 0.1 mgL−1, chemical oxygen demand (COD) ranged from 53.9 ± 4.7 26, 336.7 ± 398.0 mgL−1 while biochemical oxygen demand (BOD) ranged from 13.8 ± 0.92 to 23.3 ± 1.35 mgL−1. The mineral concentrations of P, K, Ca, Mg, Zn, Fe, Na, S, NO3, Cu, Pb, Cr ranged from below detection limit −280.13 ± 1.07 mgL−1 for SOWW wastewater, 0.04 ± 0.003-2344.02 ± 0.09 mgL−1 for MRWW wastewater and 0.017 ± 0.002–501.29 ± 0.09 mgL−1 in CFWW wastewater. All the heavy metals tested were within the permissible limits except for lead (Pb), with the value 0.103 ± 0.003 in SOWW sample. The microbial loads of the samples (total bacteria and total fungi) ranged from 0.72 x 106–13.0 x 106 and 0–14.0 x 104 respectively. The analysis revealed that there was no significance difference between the physicochemical properties and mineral compositions at p≤0.05. The water quality indices for the wastewaters irrigation suitability showed; 6.06–22.91% Sodium adsorption rate (SAR), 22.75–72.00% sodium (% Na), 9.66–31.89% soluble sodium (SSP), 7.91–29.50 magnesium absorption ratio (MR), 1.74–132.16 mg/L total dissolved solutes (TDS) and 0.11–0.46 Kelley’s ratio (KR). The findings indicated that the wastewaters were suitable for irrigation purposes except for the unsuitable values of Na % (72%) in SOWW. The overall water quality of the studied wastewaters is suitable for the growth of vegetables and other crops. This study will establish a baseline data for future research, because little/no information is available about the comparability and utilization of these wastewaters. If properly applied, these wastewaters can be used for the recycling of nutrients for vegetable irrigation, reduce pollution from indiscriminate disposal, and improve water quality.